Correlation of age and the diameter of the cervical nerve roots C5 and C6 during the first 2 years of life analyzed by high‐resolution ultrasound imaging - Linde, Jacoba; Jenny, Carole; Hundsberger, Thomas; Broser, Philip J. (Brain and behavior, 2022)
Aim To analyze the increase in diameter of the nerve roots C5 and C6 in early childhood. Methods The nerve roots of 56 children aged 0 days to 10 years (47 younger than 2 years) were examined by high‐resolution ultrasound imaging. The correlation of diameter and age was statistically tested and a logarithmic regression analysis was performed to develop a logarithmic growth model. Results The increase in nerve root diameter is greatest during the first 2 years of life and then the growth rate decreases steadily. The relationship between age and diameter follows a logarithmic curve (p < 10–8). Interpretation The main increase in the diameter of the nerve roots happens in the first 2 years of life. Comparing data from a previous study, our data also suggest that the maturation of the proximal part of the median nerve is comparable to the maturation of its distal segments. This suggests a synchronous maturation of the axons and myelin sheath for the whole extent of the nerve, from the radix to its very distal part. What This Paper Adds Normative values for the size of the cervical nerve roots C5 and C6; an insight into the maturation of the proximal parts of the peripheral nervous system; and the correlation between age and cervical root diameter. Graphical :